Analisis Manajemen Sumber Daya Manusia Guna Meningkatkan Loyalitas Pelanggan - Salsabila Nur Fadiyah; Munawaroh Munawaroh (Master Manajemen, 2025)
Human Resource Management (HRM) plays a strategic role in supporting the increase in customer loyalty as one of the indicators of business success. Customer loyalty is not only influenced by the quality of products or services, but also by the interactions carried out by employees in various business lines, such as customer service, sales, and marketing. Customer service-oriented employee training is an important aspect of this strategy. By providing the right training, employees can better understand a customer's needs, respond effectively, and create a positive, memorable experience. In addition, the development of a corporate culture that focuses on superior service and employee empowerment also contributes to increased work motivation, which has a direct impact on the quality of interactions with customers.